Lèxic de l’administració i del món rural en documentació municipal de Fraga (s. XVI) - Fort i Cañellas, M. Rosa (Caplletra. Revista Internacional de Filologia, 1999)
A study of legal-administrative and agricultural vocabulary of the minutes book of the town of Fraga between 1477 and 1505. Although this is a formal compilation, it shows many characteristics of real language in a region which constitutes a linguistic boundary. Thus, together with repetitive bureaucratic expressions, there are numerous terms of legal or rural vocabulary, coincidental with or akin to north-western Catalan and Valencian, which have eventually become part of the general language.